Overcoming the Five Dysfunctions of a Team - Lencioni, Patrick (Recorded Books, 2006)
Patrick Lencioni is the New York Times best-selling author of The Five Dysfunctions of a Team. In this follow-up to his groundbreaking work, Lencioni provides a field guide for implementing the principles of achieving corporate goals through this innovative program. The work also boasts helpful exercises and illustrative, real-world examples. "Lencioni is fast defining the next generation of leadership thinkers."-Ken Blanchard, coauthor of The One Minute Manager.